Jamie May’s Success and Bill Houston’s Failure Search for Meaning of Life in Denis Johnson’s Angel - Indreswari, Intan (LANTERN (Journal on English Language, Culture and Literature), 2014)
The purpose of this research is to analyze the meaning life of Bill Houston and Jamie May. In order to complete this paper, the writer used library research to collect the material. The writer uses a book written by Viktor Frankl about logotherapy to analyze the novel. Logotherapy consists of existential problems and the way to find the meaning of life. Existential problems fall into existential frustration, existential vacuum and noogenic neuroses. Projection and de-reflection are a therapy which is used to recover existential problem. The meaning of life can be found through deed, suffering and love. The result of the analysis shows that the true meaning of Bill and Jamie’s life are found after they feel some frustration, helpness, loneliness and love.